De Re Cervisia et Mulso, “on The Subject of Beer and Mulsum” - Matt Gibbs (EXARC Journal)
Beer has a long and ubiquitous history. Today it is the most consumed alcoholic beverage in the world; it is also the most popular drink after water and tea (Swot, 2016). But little consideration is typically given to how beer developed with respect to taste, and even less is given to why beer is thought of in the way that it is. There have been developments in this regard: the craft beer movement, something particularly relevant in many Western countries today, has provided an opportunity to reconsider the way in which beer has been mass-produced commercially, and has moved away from this model (Clapson, 2017; Weersink and von Massow, 2018).